Mentoring, Managing, and Motivating Online Course Instructors: Emerging Chair Responsibilities - Mary B. Schreiner Ph.D.; Scott Ballantyne Ed.D.; Karen Thacker Ph.D. (Academic Chairpersons Conference Proceedings, 2016)
The number of online university courses continues to grow, and instructors of these courses need unique kinds of involvement with their department chairs. The presentation outlines best practices department chairs can use to mentor, manage and motivate online course instructors, based on both experience and emerging literature in this field.
Keywords: online; technology; faculty; development; management